2018
DOI: 10.20546/ijcmas.2018.705.042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mupirocin Resistance in Methicillin Resistant Staphylococcus aureus Strains isolated from a Tertiary Care Hospital

Abstract: Mupirocin is a topical antibiotic that has been used extensively for treating methicillin resistant Staphylococcus aureus (MRSA) associated infections. However, the prevalence of resistance to mupirocin is being increasingly found due to its irrational and widespread use. Retapamulin: a pleuromutilin antibacterial agent is an effective topical antibiotic against these resistant strains. This study was carried out to determine the rates of resistance to mupirocin in MRSA isolates in our patient population, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This suggests that these antibiotics might be used to treat MRSA infections empirically. The findings were consistent with those published by Pourramezan et al, 18 , who found that Due to widespread usage of Mupirocin ointment for skin and soft tissue infections, in decolonization programs and due to MRSA being a prominent risk factor for Mupirocin resistance, higher resistance rates reported by Madhumati et al, 19 and Antonov et al, 20 (24 %) and (55.4 %) were Mupirocin resistant MRSA. however, lower resistance rate (2%) was reported by Singh et al, 21 .…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that these antibiotics might be used to treat MRSA infections empirically. The findings were consistent with those published by Pourramezan et al, 18 , who found that Due to widespread usage of Mupirocin ointment for skin and soft tissue infections, in decolonization programs and due to MRSA being a prominent risk factor for Mupirocin resistance, higher resistance rates reported by Madhumati et al, 19 and Antonov et al, 20 (24 %) and (55.4 %) were Mupirocin resistant MRSA. however, lower resistance rate (2%) was reported by Singh et al, 21 .…”
Section: Discussionsupporting
confidence: 91%